Src-1 and SP2 promote the proliferation and epithelial–mesenchymal transition of nasopharyngeal carcinoma - Zhang Jingjing (De Gruyter, 2021)
Nasopharyngeal carcinoma (NPC) is characterized by high morbidity and morality, especially in Southern China. Transcription factors intensively participate in the initiation and development of NPC. This study aimed to investigate the roles of Src-1 in NPC. mRNA level was determined by qRT-PCR. Western blot was carried out for the protein level. CCK-8 assay was performed to determine cell viability, colony formation for NPC cell proliferation, and transwell for cell migration and invasion ability. The results showed Steroid receptor coactivator 1 (Src-1) was overexpressed in SNE-2 and 6-10B. The expression of Src-1 and SP2 was in positive correlation. Overexpression of Src-1 promoted the cell viability, colony formation, and epithelial–mesenchymal transition (EMT), manifested by the increase of migration and invasion ability, while knockdown of Src-1 exerted opposite effects. Additionally, knockdown or overexpression of SP2 reversed the effects of overexpressed or downregulated Src-1, which was reversed by the depletion of SP2. Moreover, Src-1 interacted with SP2 to regulate EMT-related genes such as E-cad, N-cad, Vimentin, and ZEB1, and proliferation- and apoptosis-related genes, such as bax, cytochrome c, and cleaved caspase3 and bcl-2. Thus, blocking the interaction between Src-1 and SP2 may be a therapeutic target for inhibiting the metastasis of NPC.